PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Hutabarat, Zebath Mega; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this study is to identify the direct and indirect effects of product and service quality on the satisfaction of Catering Tabotabo. This study is categorized as an explanatory research since it explains the causal relationships between variables through hypothesis testing. Using purposive sampling technique, 70 people who have used the service of Catering Tabotabo at least twice were selected as the respondents. The data was analyzed through validity and reliability tests, and the hypotheses were assessed using F test, t test, multiple linear regression, and coefficient of determination analysis; all of which were performed in SPSS 25. This study finds that, partially, product quality does not influence customer satisfaction, while service quality significantly affects customer satisfaction. Furthermore, product quality and service quality simultaneously have significant effects on customer loyalty.